2019
DOI: 10.1038/s42005-019-0217-6
|View full text |Cite
|
Sign up to set email alerts
|

Dynamically tuned non-classical light emission from atomic defects in hexagonal boron nitride

Abstract: Luminescent defects in hexagonal boron nitride (h-BN) have recently emerged as a promising platform for non-classical light emission. On-chip solutions, however, require techniques for controllable in-situ manipulation of quantum light. Here, we demonstrate the dynamic spectral and temporal tuning of the optical emission from h-BN via moving acoustomechanical modulation induced by stimulated phonons. When perturbed by the propagating acoustic phonon, the optically probed radiative h-BN defects are periodically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 43 publications
0
38
0
Order By: Relevance
“…Recently, h‐BN is found as a natural hyperbolic material [ 12,13 ] and piezoelectric material, [ 14 ] which exhibits some novel optical and electromechanical properties. [ 12–14 ] These unique properties enable itself as a candidate for practical usages in hyperlenses, [ 12,13 ] near‐field imaging, [ 15 ] deep‐UV emitters [ 16 ] and detectors, [ 17 ] quantum optoelectronics, [ 18 ] nonlinear and stretchable optics [ 14 ] (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, h‐BN is found as a natural hyperbolic material [ 12,13 ] and piezoelectric material, [ 14 ] which exhibits some novel optical and electromechanical properties. [ 12–14 ] These unique properties enable itself as a candidate for practical usages in hyperlenses, [ 12,13 ] near‐field imaging, [ 15 ] deep‐UV emitters [ 16 ] and detectors, [ 17 ] quantum optoelectronics, [ 18 ] nonlinear and stretchable optics [ 14 ] (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…These defects can confine electronic levels within the bandgap, acting as recombination centers, causing SP light emission. Lazić et al [103] observed patterns of PL peaks spanning across a spectral band of ≈900 meV for each location on the sample. In this example, the PL peaks are centered at 2.067 (≈600 nm), 2.090 (593 nm) and 2.155 eV (575 nm), here labeled as ZPL 1 , ZPL 2 , and ZPL 3 , respectively.…”
Section: H-bn Optical Point Defects and Spssmentioning
confidence: 99%
“…An alternative method to achieve spectral tuning can be based on the use of acoustic-mechanical effects induced by radio frequency (RF) surface acoustic waves (SAW) [103,140]. h-BN flakes were transferred onto a lithium niobate (LiNbO 3 ) crystal with two interdigital transducers.…”
Section: Spectral Study and Control Of Spssmentioning
confidence: 99%
See 1 more Smart Citation
“…First studies have already shown that SAWs can be used to cause energy modulations of the optical transition. [184,185] They could also be implemented in recently fabricated hBN phononic wave guides. [186] It was also proposed theoretically how a selective phonon-assisted optical excitation of the color center could be used to deterministically create LO phonon states which change the PL spectrum.…”
Section: Artificial Atoms In Layered Materialsmentioning
confidence: 99%